iSAT Webinar with Senegal’s Agricultural Extension and Advisory Service Providers - Grossi, Amanda; Braun, Melody; Hansen, James; Trzaska, Sylwia; List, Geneva; Whitbread, Anthony M.; Joseph, Jacob Emanuel; Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A webinar on the topic of the intelligent Agricultural System Advisory Tool (iSAT) was convened with Senegal’s main public and private agricultural extension and advisory service (EAS) providers on May 4, 2023. The webinar, which was organized as part of the World Bank’s Accelerating the Impacts of CGIAR Climate Research for Africa (AICCRA) project, brought together EAS providers who were involved in the co-production, training of trainers (ToT), and upcoming pilot of the newly developed Climate Risk Management in Agricultural Extension (CRMAE) curriculum to learn more about the iSAT advisory tool incorporated within the curriculum’s Module 3 covering climate-sensitive agricultural decisions. iSAT is a climate-smart technology designed to help smallholder farmers in managing climate risks through timely, location- and crop-specific forecast-based agro-advisories.